Development of Scrapbook Learning Media in Indonesian Language Content for Class III Primary School - Marwan Pulungan; L. Laihat; Siti Dewi Maharani; Berta Herdiana; Mazda Leva Okta Safitri (Universitas Muhammadiyah Malang, 2024)
Based on the results of pre-research activities through observations and interviews conducted by researchers in class III at SD Negeri 05 Indralaya, various problems in learning activities were revealed. Scrapbooking is an example of a very interesting still visual media, referring to the art of sticking photos or drawings on paper and turning them into creative works. This research aims to produce valid and effective learning media products. Media validity, teacher response, and student response to scrapbook learning media in Indonesian language content. The type of research used is Research and Development (R&D) with the ADDIE development model with five stages consisting of Analyze, Design, Develop, Implement, and Evaluate. The research subjects were 1 teacher and 15 students. Data collection was carried out based on the results of material expert and media expert validation sheets, teacher response questionnaire sheets student responses, interviews, and documentation. Validation from material experts with a score percentage of 96.42% which is categorized as very valid. Validation from media experts with a score percentage of 90.6% which is categorized as very valid. The teacher response questionnaire resulted in a percentage score of 100% which was categorized as very good. Student response questionnaire with 2 trials, namely the small group got a percentage result of 88.88% in the very good category, and the large group got a percentage result of 84.44% in the very good category. Thus, the product in the form of scrapbook learning media is valid and effective for use as a learning media.